Solar Wind Interaction With the Martian Upper Atmosphere: Roles of the Cold Thermosphere and Hot Oxygen Corona. Issue 8 (29th August 2018) - Dong, Chuanfei; Bougher, Stephen W.; Ma, Yingjuan; Lee, Yuni; Toth, Gabor; Nagy, Andrew F.; Fang, Xiaohua; Luhmann, Janet; Liemohn, Michael W.; Halekas, Jasper S.; Tenishev, Valeriy; Pawlowski, David J.; et al.
Abstract: We study roles of the thermosphere and exosphere on the Martian ionospheric structure and ion escape rates in the process of the solar wind‐Mars interaction. We employ a four‐species multifluid magnetohydrodynamic model to simulate the Martian ionosphere and magnetosphere. The cold thermosphere background is taken from the Mars Global Ionosphere Thermosphere Model, and the hot oxygen exosphere is adopted from the Mars exosphere Monte Carlo model—Adaptive Mesh Particle Simulator. A total of four cases with the combination of 1‐D (globally averaged) and 3‐D thermospheres and exospheres are studied. The ion escape rates calculated by adopting 1‐D and 3‐D atmospheres are similar; however, the latter are required to adequately reproduce the ionospheric observations by the Mars Atmosphere and Volatile EvolutioN mission. In addition, our simulations show that the 3‐D hot oxygen corona plays an important role in preventing planetary molecular ions (O 2 + and CO 2 + ) escaping from Mars, mainly resulting from the mass loading of the high‐altitude exospheric O + ions. The cold thermospheric oxygen atom, however, is demonstrated to be the primary neutral source for O + ion escape during the relatively weak solar cycle 24. Key Points: Despite the similar ion loss rate calculated from 1‐D and 3‐D atmospheres, the latter are required to adequately reproduce MAVEN observations The hot oxygen corona plays an important role in protecting the Martian ionosphere/thermosphere from the solar wind erosion The thermospheric oxygen atom is the primary neutral source for O + ion escape during the relatively weak solar cycle 24